Angiogenesis in the corpus luteum - Wulff Christine; Fraser Hamish M (BMC, 2003)
Abstract The corpus luteum (CL) is a site of intense angiogenesis. Within a short period, this is followed either by controlled regression of the microvascular tree in the non-fertile cycle, or maintenance and stabilisation of the new vasculature a conceptual cycle. The molecular regulation of these diverse aspects is examined. The CL provides a unique model system in which to study the cellular and molecular regulation of angiogenesis. Vascular endothelial growth factor (VEGF) has been found to have a major role in the CL. By targeting its action at specific stages of the luteal phase in vivo by antagonists, profound inhibitory effects on luteal angiogenesis and function are observed.